2015
DOI: 10.1037/a0038394
|View full text |Cite
|
Sign up to set email alerts
|

Personalized drinking feedback: A meta-analysis of in-person versus computer-delivered interventions.

Abstract: Objective Alcohol misuse is a significant public health concern. Personalized feedback interventions (PFIs) involve the use of personalized information about one’s drinking behaviors and can be delivered in-person or via computer. The relative efficacy of these delivery methods remains an unanswered question. The primary aim of the current meta-analysis was to identify and directly compare randomized clinical trials of in-person PFIs and computer-delivered PFIs. Method A total of 14 intervention comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 24 publications
3
47
1
Order By: Relevance
“…These results are confirmed in a newly published Cochrane review by Kaner et al [19]. In a meta-analytical comparison of digital and in-person delivered intervention, Cadigan et al [20] found no difference between the two modalities on short-term effect (less than 4 months), while the in-person interventions had stronger long-term effects.…”
Section: Introductionsupporting
confidence: 74%
“…These results are confirmed in a newly published Cochrane review by Kaner et al [19]. In a meta-analytical comparison of digital and in-person delivered intervention, Cadigan et al [20] found no difference between the two modalities on short-term effect (less than 4 months), while the in-person interventions had stronger long-term effects.…”
Section: Introductionsupporting
confidence: 74%
“…Furthermore, effects of in-person brief interventions tend to last longer than web-based (Cadigan et al, 2014; Carey et al, 2012). Thus, we would not necessarily expect this very brief web-based intervention to have effects lasting for an extended period (e.g., over 1 year).…”
Section: Discussionmentioning
confidence: 99%
“…Single consumption‐based cut‐offs also feature in guidance to the public. Personalized feedback interventions often report the frequency of a patient's heavy drinking, relative to that of their peers and some low‐risk drinking guidelines contain advice about the number of drinks that can be consumed on a single occasion to minimize the risk of acute alcohol‐related harm . The danger of presenting an oversimplified definition of drinking that is likely to cause harm, and encouraging individuals to comply, is that those who are at risk of harm after consuming only small amounts of alcohol interpret all consumption up to the threshold as safe.…”
mentioning
confidence: 99%